Selling social change (without selling out) : - Robinson, Andy (Jossey-Bass, 2002)
In Selling Social Change (Without Selling Out) expert fundraising trainer and consultant Andy Robinson shows nonprofit professionals how to initiate and sustain successful earned income ventures that provide financial security and advance an organization's mission. Step by step, this invaluable resource shows how to organize a team, select a venture, draft a business plan, find start-up funding, and successfully market goods and services. Robinson includes critical information on the tax implications of earned income and the pros and cons of corporate partnerships. The book also addresses when to consider outsourcing, collaborating with competitors, and raising additional funds to expand the business.